Determinants of SME's depositors retention in Maybank / Nor Samsinah Yahaya, Nadhirah Aiman Ahmad Nordin and Amiza Lina Nawari - Yahaya, Nor Samsinah; Ahmad Nordin, Nadhirah Aiman; Nawari, Amiza Lina (2018)
Malayan Banking Bhd (Maybank) is experiencing a critical challenge in retaining their SME's depositors mainly in Selangor region. Their decline in deposit is alarming and worsened over the year. This has led to possibility the decrease in revenue for the performance year 2018. As such, this study has focused on examining the determinants of SME's depositor retention in Maybank. Specifically, this study investigated the influence of pricing, customer relationship, responsiveness and reliability towards retention of SME's depositors. The simple random sampling technique was used to sample 131 respondents from Selangor region namely Shah Alam, Subang and Kajang. The results of multiple regression analysis show that reliability, pricing, customer relationship, responsiveness and retention of SME's depositors are significant. Out of the four variables, pricing showed the greatest influence on retention of SME's depositors (p=0.395, /><0.05). Pricing as according to Jain & Tarannum Syed, 2017, was the main factor reason behind any customer retention that, when it is significant and able to attract a new customer, it is a higher and main issue in mounting loyalty and retaining customer. Therefore, it is suggested that Maybank to place more attention at the price mechanism as it is part of the critical strategy in retaining their SME's depositor. This includes, providing the best flexible rate of return, fair pricing and the best interest rate that eventually become the best factor which customers would views it as value thus led to SME's loyalty and eventually retaining the SME's depositors.